SPECIALIZED SUPPLIER NETWORKS AS A SOURCE OF COMPETITIVE ADVANTAGE: EVIDENCE FROM THE AUTO INDUSTRY - DYER, JEFFREY H. (Strategic Management Journal, 1996)
This study examines the relationship between interfirm asset specificity and performance in the auto industry. More specifically, I examine the extent to which differences in supplier–automaker asset specialization may explain performance differences between Japanese automakers (Nissan and Toyota) and U.S. automakers (Chrysler, Ford, General Motors). The findings indicate a positive relationship between supplier–automaker specialization and performance. In particular, the data suggest a positive relationship between interfirm human asset cospecialization and both quality and new model cycle time. Moreover, site specialization is found to be positively associated with lower inventory costs. The findings suggest that in the auto industry a tightly integrated production network characterized by proximity and a high level of human cospecialization will outperform a loosely integrated production network characterized by low levels of interfirm specialization.